Assessment of the Status of Contralateral Ear in Post-Operative Subjects of Unilateral Chronic Otorrhoea - Bhandari, Shama; Shrestha, Sulav; Paudel, Dhundi Raj (Journal of Nepalgunj Medical College, 2020)
Introduction: Chronic otitis media is one of the most common ear diseases in developing countries like Nepal and is important cause of the hearing loss. Chronic otitis media is rarely an isolated entity, because the responsible factors for its development in one ear in similar way will impact the contralateral ear, since both ears have a common “nasopharyngeal” drainage. Contralateral ear is defined as asymptomatic ear in cases of unilateral chronic otitis media. Aims: To evaluate the audiological profile of Contralateral ear in post-operative subjects of unilateral otorrhoea. Methods: Patients fulfilling criteria underwent Otoscopic examination, tuning fork test and pure tone audiometry. The findings of contralateral ear like retraction, tympanosclerotic patch (TS patch), thin, dull and atrophied tympanic membrane were noted. The final diagnosis with the type of surgery of diseased ear, as well as status of contralateral ear were entered into the proforma. All the patients were followed till three months in relation to anatomy of Tympanic membrane onotomicroscopy and pure tone audiometry respectively. Results: In postoperative cases of mucosal disease, the cases with abnormality in the contralateral ear reduced from 17 to 10 patients (30.3%) and the normal patients increased from 16 to 23 cases (69.7%). Likewise, in postoperative squamous disease, the cases with abnormality in the contralateral ear reduced from 14 to 11 patients (64.7%) and the normal patients increased from 3 to 6 cases (35.3%). Out of 50 cases, 14 cases (28%) had defective hearing while 36 cases (72%) had normal hearing in the contralateral ear respectively. Conclusion: The high incidence of occurrence of abnormality in contralateral ear indicate that both ears should be regarded as a pair. Unilateral Chronic otitis media should not be taken as a static phenomenon but as a continuous process in the other ear too.